Conspiracy culture in Stuart England : the mysterious death of Sir Edmund Berry Godfrey - McKenzie, Andrea (Studies in early modern cultural, political and social history, 2022)
Revisits the death of Sir Edmund Berry Godfrey, uncovering compelling new evidence and offering a solution to a mystery that has baffled scholars and armchair detectives for centuries.